HUBUNGAN PENDAPATAN KELUARGA DENGAN STATUS GIZI BALITA DI DESA TAMBANG WILAYAH KERJA PUSKESMAS TAMBANG KABUPATEN KAMPAR TAHUN 2019 - ERMA KASUMAYANTI (Universitas Pahlawan Tuanku Tambusai, 2020)
The nutritional status of children under five is something that determines the level of community welfare and the quality of human resources. Poverty is one of the highest causes of malnutrition, with low income conditions causing families to be unable to meet nutritional needs that have an impact on fulfilling nutrition in infants. The purpose of this study was to analyze the relationship between family income and the nutritional status of children under five in the village of Tambang, the Work Area of the Tambang Health Center in Kampar district in 2019. This study used a cross sectional design. The population in this study were all mothers who had children under five in the village of Tambang, the working area of the Tambang Health Center in Kampar district in 2019 were 278 people. With a total sample of research as many as 74 people. Sampling is done by simple random sampling. The data collection tool used is a questionnaire. Data analysis uses univariate and bivariate analysis. The results of the study found that there is a relationship between family income and the nutritional status of children under five with a p-value of 0.002. The results of this study are expected for families to meet the nutritional needs of their toddlers with the use of existing land to increase food needs and the support of community health centers in providing counseling to mothers of toddlers, especially regarding toddler nutrition